The national study of health and growth - Rona, Roberto J.; Chinn, Susan (Oxford : Oxford University Press, 1999)
The National Study of Health and Growth provides an overview that spans 25 years. It provides in a single volume, important information on trends in child growth and the wide range of factors that inhibit, prevent or support such growth.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children -- Great Britain -- Growth -- Longitudinal studies; Children -- Health and hygiene -- Great Britain -- Longitudinal studies